ENSINO-APRENDIZAGEM-AVALIAÇÃO DE ÁLGEBRA NO SÉTIMO ANO DO ENSINO FUNDAMENTAL ATRAVÉS DA RESOLUÇÃO DE PROBLEMAS: um caminho didático-pedagógico em uma escola pública estadual do Maranhão - MARTINS, Ana Célia de Jesus (2024)
This work originated from my trajectory as a teacher in Basic Education (Elementary and High School) and from my interest in exploring new possibilities for teaching Mathematics that promote better learning for students. Thus, the objective of this research was to investigate how the processes of teaching, learning, and assessment occur in relation to knowledge objects involving Algebra with seventh-grade students of Elementary School through the Teaching-Learning-Assessment Methodology of Mathematics through Problem Solving, as proposed by researchers Lourdes de la Rosa Onuchic and Norma Suely Gomes Allevato. The study provides a historical overview of Algebra teaching in Brazil, addressing its evolution, and discusses strategies for the development of algebraic thinking. Therefore, it is qualitative research, whose data were constructed through questionnaires, participant observation, and document analysis of students' written solutions to the proposed problems, and the responses given by the teacher in the questionnaires. The research revealed that the Teaching-Learning-Assessment Methodology of Mathematics through Problem Solving was fundamental in motivating students in building their learning, transforming them from passive agents into active and investigative participants. Furthermore, Problem Solving proved to be a good tool for assessment, allowing the teacher to monitor students' progress and difficulties and to plan future lessons. The educational product resulting from the research is an e-book, which includes the didactic sequence and the proposed problems, based on the studied methodology, which can be used to promote a more effective and engaging learning of Algebra in Elementary School. It was concluded that this approach significantly contributed to a good understanding of algebraic concepts and procedures.